Exploring motivational underpinnings of organizational vision – how do visions become reality? - Ahlberg, Anttu (My University, 2025)
Across the Global West, sentiment has been pessimistic lately, lacking a shared positive view of the future. Organizations play an important role in shaping sentiment by contributing to society through investments. However, companies in Finland in particular have been criticized for not investing in the future. One potential reason may be the lack of organizational vision. This research aims to explore the origins of organizational vision, how it connects to employee motivation, and how it contributes to the realization of desired long-term organizational objectives. This research considers organizational vision as a multidisciplinary construct. This research contributes to futures studies by providing a comprehensive theoretical framework for organizational vision that combines futures studies with strategy and motivational psychology literature. The framework consists of three dimensions: vision origins, vision orchestration, and vision implementation. Using a qualitative case study approach, semi-structured interviews were conducted with nine participants across three case organizations representing different industries, ownership structures, and maturity levels. The empirical evidence reveals significant variation in organizational approaches to visioning. The findings demonstrate limited capabilities and attention to organizational foresight and future orientation, which significantly hinder visioning capabilities, as these serve as prerequisites for organizational vision formation. Systematic methodologies are also lacking, indicating that vision formation relies on management intuition rather than the structured participatory approaches suggested in theory. The findings support a connection between employee motivation and organizational vision through satisfaction of basic psychological needs, establishing a link between self-determination theory and organizational vision. The basic needs of competence, autonomy, relatedness, and beneficence were examined, with competence need satisfaction gaining particular support from the findings, as organizational vision can help illustrate career paths and future employee development needs. The study findings contribute to futures studies research by identifying a methodological gap between organizational vision theory and today's organizational practices. As environments become increasingly dynamic, the research suggests that organizational vision will become a strategic imperative, serving as an organizational North Star and supporting intrinsic employee motivation and resilience.
Keywords: organizational vision, visioning, motivation, self-determination, need satisfaction, goal hierarchy